Developing Task Based English Material for Midwife Students - Adila Jefiza; Eliza Trisnadewi; Lusi Linawati (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
Vocabulary is one of language components that are important in English. This research was designed to analyze the inhibit factors of students’ English vocabulary mastery. The objective of the research is to analyze and find the inhibit factors of vocabulary mastery that experienced by the students. The method used in this research was qualitative method. While the approach that used here was case study approach. The researcher took the subject of the research from seventh graders of Global Junior High School in academic year 2017/2018. In this research, the data collection methods were used observation, questionnaire, and interview. Observation process was done when the teacher was teaching in the class. Questionnaire was given to all the students in seventh grade in Global Junior High School. Whereas Interview was done to the six randomly selected students and one English teacher. From the result of the analysis from the four instruments, the researcher found many inhibit factors that happen to the students, such as: similarity to English words already known, spelling and pronunciation, and appropriate use. The result of the research is expected to be used as reference or idea to create or develop further research. This research also can be used as reference or consideration to the institution or the teacher to improve the learning and teaching technique that can improve the students’ vocabularies